The evaluation criteria for selecting the type of fixation implant for total hip replacement - Chornyi, V. N.; Moskalkov, A. P.; Malyshev, V. V. (Zaporozhye Medical Journal, 2013)
Osteoarthrosis is a chronic disease of joints. Endoprosthetics is one of the methods of treatment of osteoarthrosis. A choice of method of fixing of implant is one of the important questions in the preoperative planning. In a clinic «Motor-Sich» conducted the analysis of operative treatment of a 41 patients. The use of cortical index and criterias of ultrasonic densitometry is described in the choice of type of endoprosthesis.